2021
DOI: 10.3390/ijms22189984
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Small Molecule Inhibitors against Staphylococcus aureus Dihydroorotase via HTS

Abstract: Drug-resistant Staphylococcus aureus is an imminent threat to public health, increasing the importance of drug discovery utilizing unexplored bacterial pathways and enzyme targets. De novo pyrimidine biosynthesis is a specialized, highly conserved pathway implicated in both the survival and virulence of several clinically relevant pathogens. Class I dihydroorotase (DHOase) is a separate and distinct enzyme present in gram positive bacteria (i.e., S. aureus, B. anthracis) that converts carbamoyl-aspartate (Ca-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Aquifex aeolicus DHOase (AaDHOase) is active only when complexed with AaATCase [ 5 ]. Given that CAD is a key enzyme for the cell’s progression through the S phase of the cell cycle and controls the cell proliferation in mammalian cells [ 6 , 7 , 8 ], these distinct differences among species may indicate that DHOase is a promising target [ 9 , 10 , 11 ] for potential antimalarial, anticancer, and antipathogen chemotherapy [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aquifex aeolicus DHOase (AaDHOase) is active only when complexed with AaATCase [ 5 ]. Given that CAD is a key enzyme for the cell’s progression through the S phase of the cell cycle and controls the cell proliferation in mammalian cells [ 6 , 7 , 8 ], these distinct differences among species may indicate that DHOase is a promising target [ 9 , 10 , 11 ] for potential antimalarial, anticancer, and antipathogen chemotherapy [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…coli [ 48 ], the HIV-1 integrase strand transfer complex [ 49 ], dihydroorotase in S . aureus [ 50 ], and most recently there has been a significant effort to target the main protease (M pro ) of SARS-CoV-2 [ 51 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified that S. purpurea-root-acetone could inhibit the enzymatic activity of huDHOase. DHOase is the third enzyme in the de novo biosynthesis pathway of pyrimidine nucleotides (Figure 7A) and is considered an attractive target for potential antimalarial, anticancer, and antipathogen chemotherapy [17,[39][40][41]43,[54][55][56][57][58][59][60][61]. This enzyme contains a binuclear metal center (Znα/Znβ) and a residue Asp1686 (Figure 7B) crucial for the catalysis [42,[62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%